Eleven new species of the genus Belisana Thorell (Araneae: Pholcidae) from South China - Zhang, Feng; Peng, Yan-Qiu (Zootaxa, 2011)
Eleven new species of the spider genus Belisana are reported from South China: Belisana galeiformis sp. nov., B. bawangensis sp. nov., B. chaoanensis sp. nov., B. diaoluoensis sp. nov., B. longinqua sp. nov., B. parallelica sp. nov., B. erromena sp. nov., B. lata sp. nov., B. colubrina sp. nov., B. tianlinensis sp. nov., and B. yangi sp. nov. Somatic and genitalic features are described and illustrated.